Examination of the Microbial Spectrum in the Etiology of Erythema Nodosum: A Retrospective Descriptive Study - Ozlem Ozbagcivan; Sevgi Akarsu; Ceylan Avci; Burcu Bahar Inci; Emel Fetil (Journal of Immunology Research)
Even though infections are the most common cause of erythema nodosum (EN), only certain microorganisms take the great interest such as streptococci in knowledge. Our aim was to examine the frequency and type of infections in EN, to determine the characteristics of patients with an infectious etiology, and to discuss the role of these microbes in EN pathology in the context of their interactions with humans. Charts of 81 patients with EN who were seen between 2003 and 2017 were retrospectively reviewed. Identified etiological factors were classified into three groups: infectious, noninfectious, and idiopathic. While there were no significant demographic and clinical differences between the infectious and idiopathic groups, systemic symptoms (p=0.034) and the number of EN lesions (p=0.016) were significantly lower; the mean erythrocyte sedimentation rate was significantly higher (p=0.049), but the mean aspartate aminotransferase value was significantly lower in the infectious group compared to the noninfectious group (p=0.019). Besides streptococci, many other microbes, including the ones living on and inside us, were identified in the etiology of EN. There is a need for large-scale prospective studies involving control groups for a better understanding of the microbial immunopathology of EN.